Aftershock: Blended Learning Difficulties Faced of Selected Senior High School Grade 12 Honor Students in Bestlink College of the Philippines S.Y. 2022-2023: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this research is to determine the difficulties faced by selected senior highschool g12 honor students of Bestlink College of the Philippines in terms of AcademicPerformance, Educational Competency, and Cognitive Behavior.The results of this study reveal that the Blended Learning difficulties faced by our respondentsare well outperformed by them as they become more resilient: academic performance showsthat they are all cooperative and open to collaboration, and using their gadgets is useful toform schoolwork and also they often share their knowledge through recitations. EducationalCompetency shows that they are a good communicator as a student; creativity andresourcefulness are some of the skills seen in them while using straight English is oftenperformed. Cognitive Behavior shows that studying is stressful yet beneficial to use it as afoundation to overcome difficulties.This study recommended encouraging students to focus on the solution, not the problemitself. Inspire students to believe that this difficulty will end soon. Also, setting a goal is a must.Furthermore, using the skills and competencies to promote changes, critical thinking BCPiansnot only flow in the mind but also in our actions or will. Applying and sharing the innovativeeffects of Blended Learning will make our School resilient.
Keywords: Social Sciences